2023
DOI: 10.2147/dmso.s413407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycemic Variability on Regulatory T Cells in Patients with Type 2 Diabetes and Kidney Disease

Abstract: Purpose To investigate the pathogenesis of diabetic kidney disease (DKD) in type 2 diabetes mellitus (T2DM), we evaluated the effects of short-term glycemic variability (GV) on the profile of T cell subpopulations. Methods A total of 47 T2DM patients with normoalbuminuria, 47 microalbuminuria, and 49 macroalbuminuria were enrolled. The continuous glucose monitoring (CGM) determined the GV of enrolled patients. Flow cytometry was used to determine the proportion of T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Obesity-associated chronic in ammation is an important factor in the predisposition to T2D 44,50 . Multiple studies have shown that an imbalance between Treg and Th17 cells, speci cally a de ciency of Tregs and an excess of Th17 cells, is linked to obesity, insulin resistance, and T2D [51][52][53] . Some studies have suggested that systemic Treg defects are associated with diabetic nephropathy, retinopathy, and diabetic foot ulcers 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-associated chronic in ammation is an important factor in the predisposition to T2D 44,50 . Multiple studies have shown that an imbalance between Treg and Th17 cells, speci cally a de ciency of Tregs and an excess of Th17 cells, is linked to obesity, insulin resistance, and T2D [51][52][53] . Some studies have suggested that systemic Treg defects are associated with diabetic nephropathy, retinopathy, and diabetic foot ulcers 54,55 .…”
Section: Discussionmentioning
confidence: 99%